Designing a sustainable digital control room for public transport: a comprehensive human performance measurement model - Amalia Suzianti (Production and Manufacturing Research: An Open Access Journal, 2022)
The control rooms of organizations such as bus rapid transports and automated railroad systems have changed from conventional systems with analogue equipment to modern systems with digital equipment. These changes have necessitated adaptations in the responses and habits of operators carrying out tasks. Although enhancing the system from conventional to modern is intended to improve the system performance, it often exerts the opposite effect. Therefore, the risk of decreased operator performance needs to be evaluated. This research develops a design framework incorporating comprehensive dimensions for evaluating operator performances in digital control rooms. The evaluation is based on the theory of ergonomics and is implemented by the analytical hierarchical process and fuzzy set theory. The framework has been empirically tested in digital control room for bus rapid transport and thus, it can be customized and implemented to design the work and workplace of digital control rooms for public transport design.